SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN KUALITAS PELAYANAN PADA MALANG DORM HOSTEL MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Purnamasari, Putri Indah; Marisa, Fitri (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2018)
The  expanding world  of  the  hospitality industry makes the  company have  to  compete tightly  to  keep  its business. Quality of  service from  a  company affects  the  level  of  customer satisfaction, If the  better the quality  of service then  the  level of customer satisfaction is higher.  Decision support system to  determine service quality at hostel dorm  hostel using SAW method can  help companies evaluate the quality of service that  has been  given.  The results of the  evaluation can  be  used to determine policies relating  to efforts to improve  service quality.  The results obtained from  the  calculation of the  weight  of the  criteria  assessment with the Fuzzy Simple Additive Weighting (SAW) method succeeded, thus obtaining the VAR score (the result of the assessment at Malang  Dorm Hostel exceeded the 4-5 star rating of the customer is good-very good.